2021
DOI: 10.1002/app.50533
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and mechanical properties of epoxy resin reinforced with modified iron oxide nanoparticles

Abstract: Epoxy polymers, having good mechanical properties and thermal stability, are often used for engineering applications. Their properties can be further enhanced by the addition of iron oxide (Fe3O4) nanoparticles (NPs) as fillers to the resin. In this study, pristine Fe3O4 NPs were functionalized with polydopamine (PDA), (3‐glycidoxypropyl)trimethoxysilane (GPTMS), and (3‐aminopropyl)trimethoxysilane (APTES). X‐ray diffraction and scanning electron microscopy (SEM) were used to study any changes in the crystal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 65 publications
(112 reference statements)
4
24
0
Order By: Relevance
“…The pure epoxy resin had an average degradation temperature (Td) of 341.53 ± 0.69°C with a residue content at 750°C of about 2.7 ± 0.15%. This value has been observed in literature as well 5,7,45 . Upon the incorporation of 0.125 wt% g‐C 3 N 4 , the value of Td increased by 8.86% to reach a maximum of 371.79 ± 0.19%.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The pure epoxy resin had an average degradation temperature (Td) of 341.53 ± 0.69°C with a residue content at 750°C of about 2.7 ± 0.15%. This value has been observed in literature as well 5,7,45 . Upon the incorporation of 0.125 wt% g‐C 3 N 4 , the value of Td increased by 8.86% to reach a maximum of 371.79 ± 0.19%.…”
Section: Resultssupporting
confidence: 83%
“…Conradi et al showed that the addition of 0.5% by volume of nanosilica to epoxy increases the material's fracture toughness by at least 25% 3,4 . Besides, the use of inorganic metal oxides such as zinc, 5 iron, 6,7 copper, 8 and aluminum oxides 9 has also proven to enhance the polymer's mechanical properties. Moreover, the use of organic nanofillers has mostly been focused on the use of fullerenes, carbon black, carbon nanotubes, graphene, and their derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the use of ceramic powders to enhance the strength of polymers has been of concern to many researchers because the results are composites with outstanding properties. There are many factors influencing the improvement, including the concentration of filler, filler size, [1][2][3][4] dispersion of filler in the matrix, 5,6 and interfacial interaction between the filler and matrix. 7,8 These effects are important for a wide range of scientific and industrial processes.…”
Section: Introductionmentioning
confidence: 99%
“…There are many methods to enhance the thermal conductivity of CF/EP composites, such as adding thermal conductive micro/nano fillers to polymer, 9 modifying fiber and interface 10 and constructing a 3D network thermal channel 11 . Adding thermal conductive fillers is a simple and efficient way to enhance the thermal conductivity of composite materials 12,13 . Hexagonal boron nitride (h‐BN) has been widely used as the thermal conductive filler due to its high thermal conductivity, low density, good stability and cost‐efficiency 14–16 .…”
Section: Introductionmentioning
confidence: 99%